1988
DOI: 10.1073/pnas.85.6.1942
|View full text |Cite
|
Sign up to set email alerts
|

Identification of specific apical membrane polypeptides associated with the antidiuretic hormone-elicited water permeability increase in the toad urinary bladder.

Abstract: Antidiuretic hormone (ADH) increases the water permeability of the toad urinary bladder. The increase occurs in the apical plasma membrane of granular cells that line the urinary surface of the bladder and is produced by the insertion of water permeability units that have been identified by freeze-fracture electron microscopy as intramembrane particle aggregates. Under water-impermeable conditions, particle aggregates reside in intracellular vesicles called "aggrephores." In response to ADH, the aggrephores fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…Many groups tried examining known channels and carriers for water transport (reviewed in van Os et al 1994). William Harris and colleagues radioactively labeled proteins on the apical surface of toad bladder exposed to antidiuretic hormones (ADH) and compared those proteins to ones labeled without ADH in an attempt to find the protein that was specifically localized on the plasma membrane in response to ADH (Harris et al 1988). Expression cloning was attempted using mRNA from various tissues that were injected into Xenopus laevis oocytes to see if there was an increase in water permeability (Zhang et al 1990).…”
Section: Early Studies Of Water Transportmentioning
confidence: 99%
“…Many groups tried examining known channels and carriers for water transport (reviewed in van Os et al 1994). William Harris and colleagues radioactively labeled proteins on the apical surface of toad bladder exposed to antidiuretic hormones (ADH) and compared those proteins to ones labeled without ADH in an attempt to find the protein that was specifically localized on the plasma membrane in response to ADH (Harris et al 1988). Expression cloning was attempted using mRNA from various tissues that were injected into Xenopus laevis oocytes to see if there was an increase in water permeability (Zhang et al 1990).…”
Section: Early Studies Of Water Transportmentioning
confidence: 99%
“…Fractionation of these labeled proteins by SDS-PAGE has identified bands of 55, 53, 17, 15, and 7 kD as appearing exclusively on the surface of ADH-stimulated water-permeable bladders. Furthermore, sequestration ofa lactoperoxidase membrane iodination mixture within retrieved WCV in intact living cells results in the 125I labeling of the same bands of 55,53,17,15, and 7 kD (53). To further identify the protein bands that are likely parts of the water channel, we have examined the ability of these proteins to interact with lipid using the Triton X-1 14 partitioning analysis.…”
Section: Vesicles Deliver and Remove Adh Water Channels From The Apicmentioning
confidence: 99%
“…We (53) and others (54) have performed detailed comparisons using membrane-impermeant probes that covalently label exposed protein domains. Fractionation of these labeled proteins by SDS-PAGE has identified bands of 55, 53, 17, 15, and 7 kD as appearing exclusively on the surface of ADH-stimulated water-permeable bladders.…”
Section: Vesicles Deliver and Remove Adh Water Channels From The Apicmentioning
confidence: 99%
“…The exact sequence of events between cAMP production and the fusion of water channels at the luminal membrane is largely unknown. However, Harris et al (125) have shown that vasopressin induced the insertion of at least 3 proteins of 55, 14-17, and 7 kDa at the apical membrane as detected by 1251 surface labeling. However, whereas one report has detected changes in the iodination patterns (126), another study failed to detect any changes in the apical membrane insertion using similar methods (127).…”
mentioning
confidence: 96%
“…The vehicle used to drive these vesicles is a protein known as dynein and is an ATP-dependent process (99)(100). Water vesicles are associated with a number of GTPbinding proteins that appear important for vesicle fusion and trafficking at the apical membrane (125). Fusion at the plasma membrane is likely involving a PLA, enzyme.…”
mentioning
confidence: 99%